Integrated Genetics and Micronutrient Data to Inform the Causal Association Between Serum Calcium Levels and Ischemic Stroke - Meng, Qiang; Huang, Lu; Tao, Kai; Liu, Yong; Jing, Jiangpeng; Wang, Wen; Qin, Huaizhou; Feng, Dayun; Cai, Qing (Frontiers in Cell and Developmental Biology, 2020)
Abstract There has been an increased interest for observational studies or randomized controlled trials exploring the impact of calcium intake on cardiovascular diseases (CVD) including coronary artery disease (CAD) and ischemic stroke (IS). However, the direct relationship between total calcium intake and CVD has not been well established, and remains controversial. Mendelian randomization (MR) studies have been performed to evaluate the causal association between serum calcium levels and CAD risk, and found that increased serum calcium levels could increase the risk of CAD. However, MR analysis found no significant association between genetically higher serum calcium levels and IS as well as its subtypes. Hence, these three MR studies reported inconsistent effects of serum calcium levels on CAD and IS. Here, we performed an updated MR study to investigate the association of serum calcium levels with the risk of IS using large-scale genome wide associations study (GWAS) datasets. We selected 14 independent genetic variants as the potential instrumental variables from a large-scale serum calcium GWAS dataset, and extracted summary statistics corresponding to the 14 serum calcium genetic variants from the MEGASTROKE consortium IS GWAS dataset. Interestingly, we found significant association between serum calcium levels and IS risk using the robust inverse-variance weighted (IVW) and penalized robust IVW methods with beta=0.243, and P=0.002. Importantly, the MR results from robust MR-Egger and penalized robust MR-Egger methods further supported the causal association between serum calcium levels and IS risk with beta=0.256, and P=0.005. Meanwhile, the estimates from other MR methods are also consistent with these above findings.